2012
DOI: 10.1002/jssc.201200706
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of alcohol markers by capillary electrophoresis

Abstract: Work dealing with the monitoring of alcohol markers by CE performed during the past two decades led to the development of assays for carbohydrate-deficient transferrin (CDT), ethyl sulfate, ethyl glucuronide, and phosphatidylethanol in body fluids and first attempts for the detection of the urinary 5-hydroxytryptophol/5-hydroxyindoleacetic acid ratio and stable hemoglobin acetaldehyde adducts. Most notably are assays for CDT that have been commercialized and are being used in many laboratories under routine co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 176 publications
0
31
0
Order By: Relevance
“…Many laboratories using the CAPILLARYS assay are currently classifying samples with CDT values >1.6% as positive, those with values <1.3% as negative, and those with CDT values between 1.3 and 1.6% as grey zone. The cutoff used for the Helena V8 assay is 1.60% whereas the cutoff values for the CEofix assays and the Verona assay are 1.8 or 1.7% . Overall, there is high correlation between data obtained by the different CZE assays and for the comparison of CZE data to those obtained by HPLC .…”
Section: Applicationsmentioning
confidence: 91%
See 2 more Smart Citations
“…Many laboratories using the CAPILLARYS assay are currently classifying samples with CDT values >1.6% as positive, those with values <1.3% as negative, and those with CDT values between 1.3 and 1.6% as grey zone. The cutoff used for the Helena V8 assay is 1.60% whereas the cutoff values for the CEofix assays and the Verona assay are 1.8 or 1.7% . Overall, there is high correlation between data obtained by the different CZE assays and for the comparison of CZE data to those obtained by HPLC .…”
Section: Applicationsmentioning
confidence: 91%
“…Other efforts revealed that resolution between the peaks of disialo‐Tf and trisialo‐Tf can have an impact on the cutoff value. With incomplete separation of disialo‐Tf and trisialo‐Tf, lower cutoff values were obtained . The cutoff value for the CAPILLARYS assay suggested by the manufacturer of the kit is 1.3%.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be detected for an extended time length after complete elimination of ethanol in blood and urine. EtG and EtS indicate recent ethanol consumption (up to 60 h) with high specificity and selectivity and thus cover a clinically and forensically important time window between short-term markers, such as ethanol, and long-term markers, such as CDT [112,113].…”
Section: Drugs Of Abusementioning
confidence: 99%
“…After a sustained intake of ethanol, PEth is accumulated in the cells and may remain in circulation for more than 2 weeks. Thus, PEth is determined in whole blood and represents a marker for long-term alcohol abuse [112,113].…”
Section: Drugs Of Abusementioning
confidence: 99%